QUESTIONNAIRE SURVEY OF FIXED CROWN PROSTHETIC TREATMENT IN CHILDREN - Mariana Dimova-Gabrovska; Desislava Dimitrova; Bozhidar Yordanov; Mariana Yankova; Todor Peev (Peytchinski Publishing, 2019)
The fixed prosthetic treatment is a method with proven high efficiency in recovering of the three medio-biological indicators. The purpose of the study is to investigate the use of laboratory crowns in children, in the daily practice of dentists in Bulgaria. Material and methods: A source of information is a specially designed questionnaire. 767 dentists from all over the country are subjected to the research. The results are statistically processed using the methods of variation, comparison and correlation analysis. Results: Dental practitioners aged 45-59 apply the laboratory crowns in childhood more often in their practice, with the largest share are those with speciality in general dentistry and in paediatric dentistry. Preferred materials for the construction of the crowns are ceramics, metal and resin. Conclusion: There is a necessity to promote the indications, methods, means, advantages and disadvantages of prosthetic treatment with laboratory-made crown constructions in childhood.